Molecular characterization of Mycobacterium tuberculosis and Mycobacterium bovis isolates by Enterobacterial Repetitive Intergenic Consensus-PCR - Caleffi-Ferracioli, Katiany Rizzieri; Baldin, Vanessa Pietrowski; Noguti, Erika Noda; Dias Siqueira, Vera Lucia; Lima Scodro, Regiane Bertin; Pavan, Fernando Rogerio [UNESP]; Hirata, Mario Hiroyuki; Cardoso, Rosilene Fressatti (Univ Sao Paulo, Conjunto Quimicas, 2018)
Tuberculosis (TB) is an infectious disease in which the molecular typing methods allow to have important information about the dynamics of transmission and to assist properly in disease control. Although the ERIC-PCR (Enterobacterial repetitive intergenic consensus-PCR) assay is fast and easy to perform, scarce studies have reported its use in epidemiological studies in TB outbreaks. In this study, we aimed to genotype Mycobacterium tuberculosis and M. bovis isolates by ERIC-PCR and compare its discriminatory power with two other classically used methods: 12 loci-MIRU (Mycobacterial Interspersed Repetitive Units) and Spoligotyping. The M. tuberculosis isolates studied were from northwestern and southwestern and M. bovis from northwestern Parana, Brazil. ERIC-PCR rendered banding patterns with great diversity (1 to 12 bands) of molecular sizes, ranging from 100 to 1600 bp. ERIC-PCR showed to be fast, simple and affordable to differentiate isolates. ERIC-PCR would be an important tool in the epidemiology of TB as screening in case of outbreak, which demands rapid intervention. However if any doubt persist, as it may occur with the application of only one genotypic method, other genotyping methods should be applied and carefully interpreted, always with additional epidemiological information.
Keywords: Tuberculosis; Molecular characterization; ERIC-PCR; Epidemiology